Community pharmacy professionals’ knowledge, attitudes, and practices toward substandard and falsified medicines and associated factors in Bahir Dar City, Northwest Ethiopia - Mekonnen, Biset Asrade; Berhanu, Kidest; Solomon, Nebiyu; Worku, Minichil Chanie; Anagaw, Yeniewa Kerie (Frontiers in Pharmacology, 2025)
BackgroundThe availability of substandard and/or falsified medicines (SFMs) in the market poses a severe threat to health and the national economy. Therefore, pharmacy professionals are highly responsible for controlling SFMs distribution in the market to improve the health of the population.ObjectiveThe aim of this study was to assess community pharmacy professionals’ knowledge, attitudes, and practices (KAP) toward SFMs and to identify associated factors in Bahir Dar City, Northwest Ethiopia.MethodsA community-based descriptive cross-sectional study was conducted from 1 August 2024, to 30 September 2024. Participants were recruited using a simple random sampling method. A structured and self-administered questionnaire was used to collect data on sociodemographic characteristics and KAP toward SFMs. The collected data were entered and analysed using SPSS version 26. Multivariate logistic regression analysis was used to identify factors associated with participants’ KAP toward SFMs. Variables with a P value < 0.05 were considered statistically significant.ResultsOf the 162 participants, 80.5% had a good knowledge and 54.9% had a positive attitude toward SFMs. However, 46.3% had a good level of practice toward SFMs. Educational levels with a master’s degree (AOR = 2.6, 95% CI: 1.06–4.35) and work experience of 21–25 years (AOR = 2.19, 95% CI: 1.79–2.80) were associated with participants’ knowledge. Educational levels with a master’s degree (AOR = 1.65, 95% CI: 0.85–2.95), work experience of 21–25 years (AOR = 1.3, 95% CI: 0.85–1.86), good knowledge (AOR: 1.21, 95% CI: 0.94–1.51), and good practice (AOR = 1.33, 95% CI: 0.85–2.01) were associated with the participants’ attitude. The practice of participants is affected by educational levels with a master’s degree (AOR = 1.2, 95% CI: 1.14–1.26), 21–25 years of work experience (AOR = 2.74, 95% CI: 1.33–5.63), good knowledge (AOR: 2.71, 95% CI: 1.50–4.92), and positive attitude (AOR = 1.06, 95% CI: 0.89–2.23).ConclusionThe study revealed that the majority of the participants had a good knowledge, and more than half had a positive attitude; however, less than half of the participants had a good level of practice toward SFMs. Education/training is required to enhance the role of community pharmacy professionals to combat their distribution and threats in the future.